Penentuan Karakter Tanaman Yang Berpengaruh Terhadap Hasil Kemiri [Aleurites moluccana (L.) Willd.] - Cici Tresniawati; Nur Kholilatul Izzah; Ilham Nur Ardhi Wicaksono; Indah Sulistyorini; Edi Wardiana (Pusat Penelitian dan Pengembangan Perkebunan, 2019)
Candlenut [Aleurites moluccana (L.) Willd.] is a perrenial plant that has high economic value. Information about vegetative and generative characters, as well as yield components that influence the yield is needed in the early stages of selection process in plant breeding. Selection of these characters can be done using Sequential Path Analysis (SPA) according to the plant development cycle, and then confirm the model using the Structural equation modeling (SEM) method. The aim of this study was to determine the vegetative characters and yield components that influence the candlenut production. The research was carried out at Pakuwon Experimental Station, Indonesian Industrial and Beverage Crops Research Institute, Sukabumi, from January to December 2018. Plant materials used in this study was 129 candlenut trees at 9 years old which were planted with a spacing of 10m x 10m. The data were analyzed using SPA followed by model confirmation using SEM method. The results showed that the production of seed was directly and positively influenced by the leaf petiole length, number of productive branches, seed weight, and number of fruits per tree, while the effect of stem height character is indirectly. Based on these results, plant selection based on vegetative characters such as leaf petiole length, number of productive branches, stem height character, number of fruits per tree and seed weight can be used to obtain high-yielding candlenut plants.